Los clivajes Estado/Iglesia y centro/periferia en el México del siglo XXI. Reflexiones respecto a la actualidad y funcionalidad de la teoría de clivajes para el caso mexicano - Rubén Torres Martínez (Amnis)
Throughout the XXth century, the Mexican hegemonic party system obscured the existence of political and social cleavages within the Mexican society. Analysts and academics never showed interest in applying the cleavages theory to a case like Mexico. From the year 2000 onwards, two historically conflicting nation projects can be observed. These projects are currently represented by two political parties: the National Action Party and the Democratic Revolution Party. Following the same logic, two existing cleavages can be observed: a) the State – Church cleavage, and b) the center – periphery cleavage, or towards Mexican nationalism. Drawing on the cleavage concept as an analysis tool allows validating existing break-up and confrontation lines in contemporary Mexico.